PENGEMBANGAN MODUL DIGITAL KONTEKS BUDAYA BUGIS TERHADAP PENGUATAN PENDIDIKAN KARAKTER DAN PENINGKATAN KEMAMPUAN LITERASI NUMERASI : PENGEMBANGAN MODUL DIGITAL KONTEKS BUDAYA BUGIS TERHADAP PENGUATAN PENDIDIKAN KARAKTER DAN PENINGKATAN KEMAMPUAN LITERASI NUMERASI - Hardianto; Makmur, Alfhian (MaPan : Jurnal Matematika dan Pembelajaran, 2024)
This study aims to determine procedures for developing digital modules in Bugis cultural context to strengthen character education and improve numeracy literacy skills that are feasible to use. The type of research used is research and development (R&D). The population of this study were fifth-grade students of SD Negeri 296 Lapaukke. The results of this study indicate that the Digital module developed using the ADDIE model through 5 stages, namely, analysis, design, development, implementation, and evaluation. Based on the results of the study, it was found that: (1) The Bugis cultural context digital module is feasible to use in improving students' numeracy literacy. This is evidenced by the calculation results of media experts by 95% (very valid) and material experts by 100% (very valid) obtained a percentage of 97.5% (very valid). The recapitulation results of the student response questionnaire are 100% (very practical). From the recapitulation of student tests, the average score is 78.4% (effective). (2) The development of Bugis cultural context digital modules on strengthening character education and improving students' numeracy literacy skills is very effective. This is evident from the numeracy literacy test results of 21 students who completed or 95% of the total number of students and there was only one student who did not complete or 5% of the total number of students. The conclusion is that the Bugis cultural context digital module is effective in strengthening character education and improving students' numeracy literacy skills.